Aerosol Gemcitabine after Amputation Inhibits Osteosarcoma Lung Metastases but Not Wound Healing. (21st January 2018) - Kleinerman, Eugenie S.; Yu, Ling; Dao, Jasmine; Hayes-Jordan, Andrea A.; Lindsey, Brock; Kawedia, Jitesh D.; Stewart, John; Gordon, Nancy
Abstract : Background . In newly diagnosed osteosarcoma (OS) patients, the time between surgery and resumption of chemotherapy is 2–7 weeks. Delays > 16 days are associated with increased risk of relapse and decreased overall survival. Identifying an effective therapy that can be used postoperatively may prevent relapse. We investigated whether aerosol gemcitabine (GCB) initiated after tumor resection inhibited the growth of OS lung metastases without affecting the wound-healing process. Methods . Mice were injected intratibially with OS cells. Amputation was performed when the tumor reached 1.5 cm. Full-thickness excisional wounds were also made on the dorsal skin and tail. Aerosol GCB or PBS was initiated 48 hours after amputation (3 times/week for 3 weeks). Wound sections were evaluated by immunohistochemistry for Ki-67 (proliferation), CD31 (vessels), VEGF, IL-10, bFGF, mast cells, macrophages, and M1/M2 macrophage ratios. The lungs were analyzed for macro- and micrometastases. Results . Aerosol GCB inhibited the growth of the lung metastases but had no effect on the 3 phases of wound healing in the dorsal skin, tail, or bone. Production of cytokines at the wound sites was the same. Conclusion . These data indicate that initiating aerosol GCB postoperatively may kill residual lung metastases thereby preventing relapse and improve survival.